(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
Children are exposed to influential role models, such as parents, peers, teachers, fictional characters and humans in virtual and physical environments. Utilising role modelling as a teaching approach or rich teaching resource not only appeals to the social learning preference of a young child but also supports teachers in reaching out to virtual and physical communities to enrich literacy learning experiences. The perspective of role models to promote acceptable social and academic behaviour in young children has progressively introduced scholarly views on the achievability and importance thereof in education and its applicability as a hybrid pedagogy. With rapid technological advancements and increased access to the Internet, an integrated platform is provided which teachers can benefit from when incorporating role models to help cultivate responsible social and academic behaviour. In this study, we implemented a literacy programme – the Reading, Rugby and Responsibility project – as a community project to improve our understanding of how rugby students, as role models, can intentionally inculcate responsible social and reading behaviour in Grade 3 children. We aligned the outcomes of the project with the Community of Inquiry framework to hypothesise the value and feasibility of using role models as a hybrid pedagogy and resource in early childhood education. We utilised a qualitative case study design and purposefully selected five rugby students to interact with 35 Grade 3 children at an inner-city primary school in Pretoria. The data generated from informal discussions with the rugby students and reflections of their experiences, as well as the children’s narrative accounts and drawings, were thematically analysed. The findings revealed that children yearn to engage with role models and be part of a community. Further investigation on how the Community of Inquiry framework can inform and utilise role modelling as a hybrid pedagogy and resource is beckoned and recommended.